Clinical evaluation of postoperative sensitivity using self-etching adhesives containing glutaraldehyde - Armando Brito Chermont; Karina Kato Carneiro; Marcelo Figueiredo Lobato; Sissy Maria Mendes Machado; Mário Honorato Silva e Souza Junior (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The present clinical study aimed to assess the postoperative sensitivity (POS) after 48 hours and seven days in occlusal restorations bonded with three different adhesive systems, two of them containing glutaraldehyde. The restorative procedures were performed using the three-step etch-and-rinse Adper SBMP-Plus adhesive (SBMP), the two-step etch-and-rinse Gluma Comfort One Bond + Desensitizer adhesive (GC+D) and the all-in-one self-etching/priming I Bond (IB) adhesive, which also has glutaraldehyde in its formula. All cavities were restored with Filtek Supreme nanoparticle composite resin. After 48 hours and seven days the patients were recalled and the postoperative sensitivity evaluated. The data analyzed by non-parametric Friedman test showed no significant differences in POS among the three tested groups after 48 hours and seven days.